Sexual education counseling: Addressing sexual attraction from a psychological and Islamic perspective - Wahidah, Fatin Rohmah Nur; Suwarti, Suwarti; Mildaeni, Itsna Nurahma; Dewi, Syavira Berliana Syaskia; Irawan, Muhammad Raynaldi Akbar Putra; Herdian, Herdian (Community Empowerment, 2021)
The purpose of this community service is to provide an understanding of the characteristics of teenagers, how to build friendships, respond to sexual attraction to the opposite sex, and how to take care of yourself physically and mentally in order to have a healthy sexual life as a true Muslim from a psychological and Islamic point of view. The methods used in this activity are lectures, quizzes and prizes, discussions, and Q&A. Pre-test and post-test were also given to participants to determine the effectiveness of the activities. The results of the activity revealed that there was an increase in participants' understanding. In other words, this counseling was effective in increasing participants' knowledge about the characteristics of adolescents and how to respond to healthy sexual attraction.